Geodynamic Characterization of the Tunja-La Playa Road Corridor (2010)
The main objective of the investigation was to determine in the Tunja-La Playa road corridor the areas susceptible to mass removal phenomena, caused by seismic-type events, and to perform the liquefaction analysis for the deposits present. After processing the information, it was determined that the corridor presents very specific sectors where the susceptibility to mass removal phenomena is high, mainly affected by topography and soil type. Likewise, in the liquefaction analysis it was determined that there is a high susceptibility in the fluviolacustres deposits in the north of the city of Tunja, which are attenuated by the great distance between these sites and the analyzed synogenic sources.